2014
DOI: 10.1007/s00383-014-3624-5
|View full text |Cite
|
Sign up to set email alerts
|

Are paediatric operations evidence based? A prospective analysis of general surgery practice in a teaching paediatric hospital

Abstract: The present study shows that nowadays a remarkable number of paediatric surgical procedures are supported by high level of evidence. Despite this improvement in evidence-based paediatric surgical practice, more than a third of the procedures still lack sufficient evidence-based literature support. More RCTs are warranted to support and direct paediatric surgery practice according to the principals of EBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…The prospective RCT performed to eliminate selection, allocation, and performance bias has been established as the highest level of evidence [5]. We previously reported that although evidence-based paediatric surgical practice has improved over the years, more than a third of the surgical procedures still lack sufficient evidence-based literature support [22]. With the present study, we confirmed that appendectomy and pyloromyotomy were supported by RCTs performed in…”
Section: Discussionsupporting
confidence: 83%
“…The prospective RCT performed to eliminate selection, allocation, and performance bias has been established as the highest level of evidence [5]. We previously reported that although evidence-based paediatric surgical practice has improved over the years, more than a third of the surgical procedures still lack sufficient evidence-based literature support [22]. With the present study, we confirmed that appendectomy and pyloromyotomy were supported by RCTs performed in…”
Section: Discussionsupporting
confidence: 83%
“…Modern medicine increasingly places emphasis on evidence-based medicine, 43 defined by Sackett et al as "(…) the conscientious, explicit and judicious use of current best evidence in making decisions about the care of individual patients." 44 Nonetheless, the paucity of high-level evidence in the literature on pediatric surgical procedures was highlighted in 1999, when Hardin et al 45 reported that only 0.3% of the literature relevant for pediatric surgery consisted of CEBM level-1 evidence studies.…”
Section: Rct Rctmentioning
confidence: 99%
“…Pediatric Surgery is a specialty characterized by the rarity of the conditions treated and the infrequency of complex procedures performed by a single surgeon in a year. This is one of the reasons why the surgical practice within this specialty lacks sufficient evidence-based literature support, 7 and why practice surveys are an effective tool for data gathering on the views, practice, and management of pediatric surgeons. The pediatric surgical literature contains hundreds of surveys, many of which have been promoted by surgical societies and administered at the annual meeting.…”
Section: Value Of Surveys In Pediatric Surgerymentioning
confidence: 99%